2006
DOI: 10.1159/000106427
|View full text |Cite
|
Sign up to set email alerts
|

Short Schedule of Cisplatin and Vinorelbine: A Dose-Finding Study in Non-Small-Cell Lung Cancer

Abstract: Objectives: A dose-finding study of a new cisplatin/vinorelbine schedule was done to increase activity of the combination, and improve compliance of non-small-cell lung cancer patients. Methods: Beginning with cisplatin 40 mg/m2 on days 1, 2 and vinorelbine 20 mg/m2 on days 1, 3, increasing dose levels up to the maximum tolerated dose (MTD) were tested in a series of 6-patient cohorts. If 3 of 6 patients experienced dose-limiting toxicity in the first 3 cycles, the previous dose was consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…The occurrence of anorexia was also slightly less in the present study compared with other studies. 7,12 The frequency of constipation in the present study was 17.4%, and it is almost consistent with findings of the studies by Zucali et al 17 and by Surendiran et al 7 Though the study by Surendiran et al 7 reported diarrhea as an adverse reaction, the present study did not observe such effect. The hematological disturbances documented in the present study was lower, compared to other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The occurrence of anorexia was also slightly less in the present study compared with other studies. 7,12 The frequency of constipation in the present study was 17.4%, and it is almost consistent with findings of the studies by Zucali et al 17 and by Surendiran et al 7 Though the study by Surendiran et al 7 reported diarrhea as an adverse reaction, the present study did not observe such effect. The hematological disturbances documented in the present study was lower, compared to other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The hematological disturbances documented in the present study was lower, compared to other studies. 12,13,17,18 However, the frequency of anemia was almost similar with the study by Zucali et al 17 The study by Surendiran et al, 7 did not report any hematological disturbances. The frequency of increased levels of serum creatinine reported in this study was less than that observed in other previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Platinum compounds still are used largely in treatment protocols for patients with advanced NSCLC in combination with other regimens. [26][27][28] Furthermore, novel treatments that target the glutathione pathway currently are under investigation. 29,30 On the basis of our results, the expression of GST-pi, P-gp, or both proteins may contribute to a more accurate prediction of outcome, giving the opportunity for better selection of patient-oriented therapy.…”
Section: Discussionmentioning
confidence: 99%